Use and function of metaphorical discourse in 1 Maccabees : Septuagint conference articles (LXXSA 2014) - Tilly, Michael (Journal for semitics, 2015)
In the poetic passages of 1 Maccabees, the narrated events are summarized and interpreted from the perspective of a third-person omniscient narrator. In these passages metaphorical speech is prominent. This article examines the functions of these metaphors within their literary contexts and investigates which social, cultural and religious conditions are recognized as integral parts of the "cultural encyclopaedia" of the ancient Jewish author and his addressees.